FAKTOR-FAKTOR YANG MEMPENGARUHI PERGANTIAN AUDITOR (Studi empiris pada perusahaan manufaktur di BEI tahun 2010-2012) (Students' Journal of Accounting and Banking, 2014)
This study aims to find empirical evidence the size of firm, the size of the client company, the growth rate of the client company, the financial condition of the client company, audit opinion, and audit fee that influence the auditor switches in Indonesia. The data used is the companies listed in Indonesia Stock Exchange (IDS) in 2010-2012 with a total sample of 144 companies. The data collection method used is purposive sampling. Data were analyzed using logistic regression. The result showed that the audit fee has a significant positive effect on auditor switches. While  the growth rate of the client company, the financial condition of the client company and the audit opinion has a positive effect and no significant on auditor switches, and the size of firm and the size of the client company has negative effect and no significant on auditor switches.Keywords: Auditor switches, the size of firm, the size of the client company, the growth rate of the client company, the financial condition of the client company, audit opinion dan audit fee